2000
DOI: 10.1007/bf03043667
|View full text |Cite
|
Sign up to set email alerts
|

Arvicola mosbachensis (Schmidtgen 1911) of Mosbach 2: a basic sample for the early evolution of the genus and a reference for further biostratigraphical studies

Abstract: Arvicola materials from Mosbaeh 2, including the types of A. mosbachensis housed at the Forschungsinstitut Senckenberg Frankfurt am Main, are described. Six specimens display incipient root development. This population is therefore one of the oldest of the genus Arvicola. This is confirmed by SDQ and tooth length values indicating a primitive evolutionary stage. The age of the population correlates with either Cromer lnterglacial III or IV.The type material of Arvicola cantianus consists of a few fragmentary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 5 publications
4
38
0
6
Order By: Relevance
“…Lower values of the index (less than 100), such as these, are typical for geologically younger (Late Glacial and Holocene) and recent populations of Arvicola terrestris (Heinrich 1978(Heinrich , 1987. The dimensions of M 1 (average length greater than 4 mm) are also in agreement with the proposed young age of the populations from Baranica (the older populations had a somewhat smaller M 1 ; Maul et al 2000).…”
Section: Systematic Paleontologysupporting
confidence: 84%
See 1 more Smart Citation
“…Lower values of the index (less than 100), such as these, are typical for geologically younger (Late Glacial and Holocene) and recent populations of Arvicola terrestris (Heinrich 1978(Heinrich , 1987. The dimensions of M 1 (average length greater than 4 mm) are also in agreement with the proposed young age of the populations from Baranica (the older populations had a somewhat smaller M 1 ; Maul et al 2000).…”
Section: Systematic Paleontologysupporting
confidence: 84%
“…A gradual increase in length of this tooth was already well documented in many European populations (Maul et al 2000). According to Heinrich (1987), an average length of M 1 greater than 4 mm is characteristic for populations from the Late Weichselian.…”
Section: Age Of the Faunamentioning
confidence: 79%
“…It means that the development of arvicolid teeth is not a chaotic process, but limited to their morphology, which, together with the natural selection, is a guide mechanism for the evolution of this group. Th is is clearly visible in morphology of late Miocene rodents (Chaline, 1987;Chaline, Graf, 1988;Fejfar et al, 2011), and justifi ed for molars in the evolutionary lineage Allophaiomys-Microtus or Mimomys-Arvicola (Rabeder, 1981;Heinrich, 1990;Rekovets, 1990Rekovets, , 1994Maul et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…This evidence suggests that the transition from Mimomys to Arvicola in Western Europe took place before the end of the Cromerian Complex. Furthermore, the persistence of Arvicola throughout the Calcareous Member at Westbury and in later deposits at Boxgrove shows that the early (pre-MIS 12) part of the Arvicola Biozone must represent a long period of time with major climatic fluctuations, including at Recent analysis of the small mammals from Isernia, Italy (Koenigswald and van Kolfschoten, 1996) and Mosbach 2, Germany (Maul et al, 2000) has identified a transitional stage in the evolution of Arvicola from Mimomys. At these sites, the adult water vole molars are unrooted, but several show closure of the crown base, which indicates that crown formation had ceased in some adult individuals (Koenigswald and van Kolfschoten, 1996, Fig.…”
Section: The Age Of the West Runton Freshwater Bedmentioning
confidence: 99%
“…This stage in the formation of roots is found in the molars of young individuals of Mimomys from West Runton, but in the Mosbach and Isernia assemblages closure of the crown base forms late in development and is found only in some older individuals. The Isernia and Mosbach 2 water voles have been assigned to Arvicola (Koenigswald and van Kolfschoten, 1996;Maul et al, 2000), but arguments could be advanced for their inclusion in Mimomys . Significantly, molars with closure of the crown base are not found in the very large Arvicola samples from Miesenheim I, Westbury Cave (Calcareous Member) or Boxgrove.…”
Section: The Age Of the West Runton Freshwater Bedmentioning
confidence: 99%